2021
DOI: 10.1016/j.xjidi.2021.100055
|View full text |Cite
|
Sign up to set email alerts
|

Solar UVR and Variations in Systemic Immune and Inflammation Markers

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…CCL4, also known as MIP-1β, is a cytokine involved in attraction of leukocytes toward inflamed skin sites. Interestingly, Mai et al (2021) reported an inversed association between blood CCL4 levels and solar UVR exposure in a population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…CCL4, also known as MIP-1β, is a cytokine involved in attraction of leukocytes toward inflamed skin sites. Interestingly, Mai et al (2021) reported an inversed association between blood CCL4 levels and solar UVR exposure in a population-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Martincorena et al utilized genomic sequencing to show that prolonged sun exposure leads to mutations in keratinocytes long before the appearance of precancerous lesions and squamous skin carcinomas [24]. Thus, at the epithelial level, DNA changes and prolonged exposure to the sun are associated with the development and progression of certain cancers [25,26].…”
Section: Discussionmentioning
confidence: 99%